Long‐term outcomes for newly‐diagnosed multiple myeloma patients treated with pegylated liposomal doxorubicin and bortezomib: final results of CALGB (Alliance) 10301, a multicentre phase II study. (22nd July 2015) - Voorhees, Peter M.; Orlowski, Robert Z.; Mulkey, Flora; Watson, Peter; Geyer, Susan; Sanford, Ben L.; Bennett, Elizabeth; Chanan‐Khan, Asher A.; Bloomfield, Clara D.; Larson, Richard A.
Summary Long‐term outcomes and updated clinical efficacy and safety data were evaluated for newly‐diagnosed multiple myeloma patients treated on a phase II study of bortezomib and pegylated liposomal doxorubicin (PegLD). Out of 61 patients, the overall response rate was 57% and the near‐complete/complete response rate was 7%. Patients aged ≥65 years old had a higher incidence of treatment‐related ≥Grade 3 non‐haematological toxicity (80% vs. 51%, P = 0·020). Median overall survival was 5·6 years and negatively impacted by the presence of International Staging System stage III disease, underscoring the need for novel treatment strategies for this group of patients.